Penerapan Life Cycle Assessment untuk Kajian Dampak Lingkungan Pada Instalasi Pengolahan Air Bersih - Muhammad Purnama Adji; Munawar Ali (Journal Serambi Engineering, 2024)
Water Treatment Plants (WTP) are an important component in providing drinking water that is safe and meets health standards. However, the process can have ainegativeiimpactionitheienvironment dueito theiuse ofichemicals and electrical energy. This research uses the Life Cycle Assessment (LCA) methodiwithitheihelpiof SimaPro software to analyze the environmental impact of WTP. The research aims to analyze the environmental impact of the clean water treatment process and offer an environmentally friendly alternative to WTP. The LCA method is used with environmental impact assessment using SimaPro 9.0. This research includes determining objectives and scope, data collection (Life Cycle Inventory), impactianalysis (Life Cycle Impact Assessment), and dataiinterpretation. The resultsiof theianalysis show that the reservoir and lamella units are the biggesticontributorsito theiimpact in the endpoint impact category. The Impact 2002+ and ReCiPe 2016 methods produced different impacts, with ReCiPe 2016 showing a higher impact in some categories. This research provides insight into the environmental impacts of the clean water processing process at WTP. Recommendations for improvement include reducing the use of chemicals, energy efficiency, and implementing environmentally friendly technology.